(untitled) (Research, Society and Development, 2026)
The consumption of higher-quality, sustainably produced food is a growing demand of the consumer market and represents an essential strategy for preserving natural resources and maintaining soil quality. This sustainable paradigm has driven the expansion of the bio-input market, such as inoculants based on beneficial microorganisms, among which plant growth-promoting bacteria (PGPB) stand out. Among the PGPB, those of Pseudomonas genus show potential to promote plant growth even in the seedling stage, providing greater protection and resilience against plausible practices and diseases present in the soil, as distributed in lettuce cultivation. Lettuce, in turn, is the most commercially traded leafy vegetable in Brazil, and its cultivation is in a constant process of innovation. Despite the economic and agronomic relevance of lettuce, studies demonstrating the positive effects of PGPB of Pseudomonas genus on the production of seedlings are still scarce. This study evaluated the effect of 21 Pseudomonas strains on lettuce seedling production, as well as the potential of these strains to synthesize metabolites associated with plant development. The 21 strains tested, 78 % stimulated greater shoot and root growth, while at least 71 % produced at least one metabolite capable of promoting plant growth. This study characterized and selected Pseudomonas strains for potential use in bioprospecting bacteria to produce bio-inputs for more sustainable agriculture.